Mobile-Assisted Pronunciation Learning: Exploring the Role of Apps in EFL University Students’ Pronunciation Development - Kholid, M. Ridho; Reftyawati, Dian (Journal of Linguistics and Social Sciences, 2025)
This study aimed to investigate the effectiveness of mobile applications in improving English pronunciation skills among university-level EFL learners. As pronunciation remains a persistent challenge for many English as a Foreign Language (EFL) students, especially in non-native speaking environments, the integration of mobile-assisted language learning (MALL) tools has gained increasing attention. This research focused on how mobile applications could support learners in developing clearer and more intelligible English pronunciation. A qualitative approach was employed to explore students’ experiences using pronunciation-focused mobile apps such as ELSA Speak and Say It. Participants consisted of 20 English Education students at UIN Raden Intan Lampung who used the applications over a six-week period. Data were collected through semi-structured interviews, learning journals, and pronunciation performance recordings. Thematic analysis was conducted to identify key patterns related to learner engagement, perceived benefits, and challenges encountered during the mobile-assisted pronunciation learning process. Findings revealed that students generally perceived mobile applications as effective tools for practicing pronunciation independently. Key improvements were noted in segmental features such as vowel and consonant accuracy, as well as suprasegmental features like word stress and intonation. Participants also reported increased confidence in speaking and greater awareness of their pronunciation errors. However, limitations such as inconsistent feedback, technical issues, and a lack of interaction with native speakers were also identified. Overall, the study highlights the potential of mobile apps as supplementary tools in pronunciation instruction and recommends their integration into EFL learning contexts to enhance oral proficiency.